Hydrocarbon gas generation characteristics of organic-rich shale and its influence on organic matter pore formation and evolution—a case study of pyrolysis experiment on the Dalong Formation shale - Zhang, Xiaotao; Xu, Xuemin; Shen, Bin; Xu, Zhichao; Yang, Jiajia; Qin, Jing; Hu, Caizhi; Li, Shizhen; Cao, Taotao; Huang, Yanran; Tian, Tao (Frontiers in Earth Science, 2025)
Shale pore structure and gas resource evaluation are greatly influenced by the development and evolution of organic matter (OM) pores, which are controlled by the process of hydrocarbon generation. In this paper, hydrocarbon gas generation and OM pore evolution were investigated on a low mature Dalong Formation shale (Ro = 0.78%, TOC = 10.40%) by the high-temperature high-pressure simulation experiments. Results indicated that hydrocarbon gas production rate show a slight increase when Ro < 2.0% and then a rapid increase when Ro > 2.0%. BET surface area and pore volume of the simulated samples increase significantly with the increases of conversion of TOC, thermal maturation level and hydrocarbon production rate, suggesting that the hydrocarbon gas generation process controls the development of OM pores. With increased Ro value, OM pores are primarily developed in amorphous kerogen and solid bitumen at wet gas generation stage and dry gas generation stage, respectively. The BET surface area and pore volume normalized to TOC can be comparable to that of naturally evolved pure kerogen of Niutitang Formations at high maturity stage. After Soxhlet extraction, BET surface area and pore volume generally have significant increase, particularly at main oil generation (Ro = 1.32%) and wet gas generation stages (Ro = 1.83%), due to that the nanometer-sized OM pores are exposed after extraction. Accordingly, an integrated model of OM pore evolution in organic-rich shale was established, and OM pore evolution can be divided into three stages: initial development stage, rapid development stage and slightly destruction stage. The three stages correspond respectively to the three stages of hydrocarbon generation: liquid hydrocarbon to wet gas generation stage, dry gas generation stage, and gas depletion stage. This study further indicates that shale with extremely high maturation degree still has better OM pore development and shale gas potential.